An intronic micro-deletion impacts the transcription and translation of PKD1 gene - Zheng, Wei; Xing, Xinli; Sun, Xuejing; Wei, Na (Frontiers in Genetics, 2026)
Polycystin-1 (PC1), encoded by the PKD1 gene, forms a complex with polycystin-2 (PKD2; 173910) that regulates multiple signaling pathways to maintain normal renal tubular structure and function. Mutations in the PKD1 gene are the primary cause of type 1 PKD (polycystic kidney disease), accounting for 78%–85% of all PKD cases. In this study, we report a case of a boy presenting with microscopic hematuria with multiple renal cysts and carrying an unreported intronic variant, c.12445-34_12445-10del, in the PKD1 gene inherited from his father who also presented PKD. Sanger sequencing and reverse transcription polymerase chain reaction (RT-PCR) for minigene splicing assays showed two abnormal splicing alterations with the c.12445-34_12445-10del variant at the mRNA level: one causes a 16-bp deletion in exon 46, resulting in premature protein termination (p.Phe4149GlyfsTer45), and the other results in a 205-bp deletion, leading to delayed termination (p.Phe4149ProfsTer139). Based on the clinical characteristics and gene mutations with functional verification, the patient was finally diagnosed with PKD caused by PKD1 function defection, as confirmed by the combined clinical features and genetic analysis. Management strategies include dietary management, blood pressure monitoring, and regular follow-up of kidney function. This is the first study to report an intronic deletion in the PKD1 gene that influences alternative splicing. Our findings expand the mutation spectrum leading to PKD1-related diseases and highlight the importance of genetic counseling for the family.